2006
DOI: 10.1055/s-2006-933559
|View full text |Cite
|
Sign up to set email alerts
|

Etiopathogenesis of Primary Sclerosing Cholangitis

Abstract: The etiopathogenesis of primary sclerosing cholangitis (PSC) remains undefined. Immunopathogenetic mechanisms appear to be involved, based on human leukocyte antigen complex susceptibility associations, existence of multiple autoantibodies, and presence of inflammatory bowel disease in > 75% of patients. PSC may represent an autoimmune disease with atypical features or an immune-mediated inflammatory disease, similar to inflammatory bowel disease itself. Immunogenetic susceptibility is closely linked to ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(98 citation statements)
references
References 101 publications
(139 reference statements)
3
91
0
4
Order By: Relevance
“…To support and expand these findings, mRNA was isolated from control and SGVHD livers and analyzed by real-time PCR for T H 17 and T H 1 cytokines and inflammatory mediators that are associated with mucosal/liver inflammation. In the SGVHD liver, there was a significant increase in mRNA for IFN-␥ (P ϭ 0.0009) as previously published in this model (19) and as demonstrated clinically (42). Since T H 17 cells have been shown to be elevated in IBD (20,27) and in the SGVHD liver (Fig.…”
Section: Increased Inflammatory Mediators In Livers Of Sgvhd Mice Itsupporting
confidence: 85%
See 1 more Smart Citation
“…To support and expand these findings, mRNA was isolated from control and SGVHD livers and analyzed by real-time PCR for T H 17 and T H 1 cytokines and inflammatory mediators that are associated with mucosal/liver inflammation. In the SGVHD liver, there was a significant increase in mRNA for IFN-␥ (P ϭ 0.0009) as previously published in this model (19) and as demonstrated clinically (42). Since T H 17 cells have been shown to be elevated in IBD (20,27) and in the SGVHD liver (Fig.…”
Section: Increased Inflammatory Mediators In Livers Of Sgvhd Mice Itsupporting
confidence: 85%
“…ϩ T cells (42). Initial studies demonstrated that SGVHD-mediated colon inflammation could be mediated by T H 17 or T H 1 immune responses Fig.…”
Section: Increased Inflammatory Mediators In Livers Of Sgvhd Mice Itmentioning
confidence: 99%
“…These notions suggest that additional pathogenetic factors may exist (e.g. bile acid toxicity [18] ), and to what extent and at what disease stage autoimmune mechanisms contribute to the bile duct damage observed in PSC is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Many antibodies have been detected in PSC patients with varying prevalences, including antinuclear antibodies (24-53%), smooth muscle antibodies (13-20%), anti-perinuclear cytoplasmic antibody ( 65-88%) (Mulder et al, 1993;Bansi et al, 1996;Terjung & Spengler, 2005;Terjung et al, 2000). However, in contrast to other autoimmune diseases, PSC is more frequently encountered in male subjects, and it does not respond to immunosuppressive therapy (O'Mahony & Vierling, 2006). One hypothesis that aims to explain the increased incidence of PSC in IBD patients postulates that the transportation of bacterial endotoxins from the inflamed colonic mucosa to the liver via the portal circulation stimulates the Kupffer cells (Fausa et al, 1991;Aoki et al, 2005).…”
Section: Pathogenesismentioning
confidence: 99%